2016
DOI: 10.1038/ncomms10258
|View full text |Cite
|
Sign up to set email alerts
|

The KDM3A–KLF2–IRF4 axis maintains myeloma cell survival

Abstract: KDM3A is implicated in tumorigenesis; however, its biological role in multiple myeloma (MM) has not been elucidated. Here we identify KDM3A–KLF2–IRF4 axis dependence in MM. Knockdown of KDM3A is toxic to MM cells in vitro and in vivo. KDM3A maintains expression of KLF2 and IRF4 through H3K9 demethylation, and knockdown of KLF2 triggers apoptosis. Moreover, KLF2 directly activates IRF4 and IRF4 reciprocally upregulates KLF2, forming a positive autoregulatory circuit. The interaction of MM cells with bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 66 publications
5
73
0
Order By: Relevance
“…29 However, our data suggested that IRF4 is not an essential target of KDM3A, at least in hypoxia, for the following reasons. First, although KDM3A expression was very weak in normoxia, but markedly increased in hypoxia, IRF4 expression was suppressed by hypoxia.…”
Section: Knockdown Of Kdm3a Induces Apoptosis In Myeloma Cells Under mentioning
confidence: 72%
See 3 more Smart Citations
“…29 However, our data suggested that IRF4 is not an essential target of KDM3A, at least in hypoxia, for the following reasons. First, although KDM3A expression was very weak in normoxia, but markedly increased in hypoxia, IRF4 expression was suppressed by hypoxia.…”
Section: Knockdown Of Kdm3a Induces Apoptosis In Myeloma Cells Under mentioning
confidence: 72%
“…Demethylated H3K9 is known to increase transcriptional activity, 34 and several transcriptional targets of KDM3A in cancer have been identified. 24,29,35 However, most of the "hypoxiaspecific" transcriptional targets of KDM3A are unknown in myeloma oncogenesis. Our data suggested that MALAT1 could be a target of KDM3A in myeloma oncogenesis under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a number of studies have implicated KDM3A (JMJD1A/JHDM2A), a member of the KDM3 subfamily with specificity for removal of mono and di-methyl marks from H3K9, in tumor/metastasis promotion, chemoresistance and other phenotypes, in cancers of epithelial origin (including the common cancers of breast 4 , prostate 5 and colon 6 ), liver 7 , and the hematopoietic system 8 . Additionally, recent studies have implicated KDM3A in solid malignancies of childhood, including the metastasis of neuroblastoma 9 , a malignant pediatric tumor of peripheral nervous system origin, and both tumorigenesis and metastasis of Ewing Sarcoma 10, 11 , a pediatric sarcoma of bone and soft tissue.…”
Section: Epigenetic Mechanisms In Cancer and Kdm3amentioning
confidence: 99%